2021
DOI: 10.1038/s41598-021-83762-4
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated viral quasispecies with a genotype-related pattern of mutations in the hepatitis B X gene of HBeAg-ve chronically infected patients

Abstract: Patients with HBeAg-negative chronic infection (CI) have not been extensively studied because of low viremia. The HBx protein, encoded by HBX, has a key role in viral replication. Here, we analyzed the viral quasispecies at the 5′ end of HBX in CI patients and compared it with that of patients in other clinical stages. Fifty-eight HBeAg-negative patients were included: 16 CI, 19 chronic hepatitis B, 16 hepatocellular carcinoma and 6 liver cirrhosis. Quasispecies complexity and conservation were determined in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Interestingly, these 3 conserved sequence fragments almost overlapped with hyper-conserved sequence fragments described in a previous study carried out by our group at circulating DNA quasispecies level (1255-1286, 1545-1573 and 1575-1603)[ 13 ]. Likewise, a recently published study by our group[ 14 ] also performed in HBV-DNA quasispecies, reported some of these hyper-conserved regions (1258-1286 and 1575-1605). In addition, these 2 previous studies[ 13 , 14 ] also reported as hyper-conserved the sequence stretch between positions 1519-1543, which we found among the 5% most conserved windows at HBV-DNA quasispecies level but not at HBV-RNA quasispecies level.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Interestingly, these 3 conserved sequence fragments almost overlapped with hyper-conserved sequence fragments described in a previous study carried out by our group at circulating DNA quasispecies level (1255-1286, 1545-1573 and 1575-1603)[ 13 ]. Likewise, a recently published study by our group[ 14 ] also performed in HBV-DNA quasispecies, reported some of these hyper-conserved regions (1258-1286 and 1575-1605). In addition, these 2 previous studies[ 13 , 14 ] also reported as hyper-conserved the sequence stretch between positions 1519-1543, which we found among the 5% most conserved windows at HBV-DNA quasispecies level but not at HBV-RNA quasispecies level.…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, a recently published study by our group[ 14 ] also performed in HBV-DNA quasispecies, reported some of these hyper-conserved regions (1258-1286 and 1575-1605). In addition, these 2 previous studies[ 13 , 14 ] also reported as hyper-conserved the sequence stretch between positions 1519-1543, which we found among the 5% most conserved windows at HBV-DNA quasispecies level but not at HBV-RNA quasispecies level. Conversely, we identified the sequence stretch 1559-1587 as hyper-conserved only in HBV-RNA quasispecies.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Recent studies have revealed that different HBV subgenotypes show different patterns of mutations, including drug-resistant mutations [30,31]. For example, Li et al [31] demonstrated that lamivudine-and adefovir-resistance-associated mutational patterns were different between subgenotypes B2 and C2 in HBV-infected Chinese patients.…”
Section: Discussionmentioning
confidence: 99%